An unusual presentation of Wilson's disease in childhood: nodular fatty infiltration in liver - Kuloğlu, Zarife; Kansu, Aydan; Demirçeken, Fulya; Erden, Esra; Fitoz, Suat; Girgin, Nurten (The Turkish Journal of Pediatrics, 2008)
Wilson's disease is a rare inherited disorder characterized by progressive accumulation of copper in the body tissues. Liver and brain are the most commonly involved organs and the disease is presented predominantly by hepatic manifestations in childhood. Histopathological findings of hepatic involvement may vary from steatosis to end stage cirrhosis. Although diffuse fatty infiltration is a typical finding of Wilson's disease, it can very rarely present in nodular pattern. We report the first case with Wilson's disease who presented with nodular fatty infiltration in the liver in childhood.